Effects of Bacillus subtilis on Candida albicans: biofilm formation, filamentation and gene expression - Silva, Michelle Peneluppi; de Barros, Patrícia Pimentel; Jorjão, Adeline Lacerda; Rossoni, Rodnei Dennis; Junqueira, Juliana Campos; Jorge, Antonio Olavo Cardoso (Brazilian Dental Science, 2019)
Objective: The aim of this study was evaluate the effect of Bacillus subtilis on Candida albicans biofilm formation and filamentation by evaluating the gene expression of ALS3, HWP1, BCR1, EFG1 and TEC1. Material and Methods: Mixed (C. albicans / B.subtilis) and monotypic biofilms were cultured in plates at 37°C for 48 h under shaking for counting viable cells (CFU / mL) and analysis of gene expression by real-time PCR. The C. albicans filamentation assay was performed in medium containing 10% fetal bovine serum at 37°C for 6 hours. Data was analysed by t-Student and Mann– Whitney tests. Results: B. subtilis reduced the biofilm formation of C. albicans in 1 log when cultured in the same environment (p<0.0001). In addition, it significantly reduced the yeast -hypha transition affecting the morphology of C. albicans. Among all of the analyzed genes, the ALS3 and HWP1 genes were the most affected, achieving 111.1- and 333.3- fold decreases in the C. albicans biofilms associated with B. subtilis, respectively. Conclusion: B. subtilis reduced the biofilm formation and filamentation of C. albicans by negatively regulating the ALS3, HWP1, BCR1, EFG1 and TEC1 genes that are essential for the production of biofilm and hyphae. Keywords Bacillus subtilis; Candida albicans; Biofilm; Filamentation; Gene expression.